EFEKTIVITAS MASSAGE KNEADING COUNTERPRESSURE SERTA KOMBINASI KNEADING DAN COUNTERPRESSURE TERHADAP PENURUNAN INTENSITAS NYERI PADA INPARTU KALA I FASE AKTIF - Febthia Rika; Asmaurika Pramuwidya; Dianna Dianna; Rakhmawati Rakhmawati (STIKes Al-Insyirah Pekanbaru, 2022)
Pain is a form of discomfort defined in various perspectives. The pain experienced during labor is different for each mother. Some labor pain management is mostly a medical procedure. Sungai Kakap Health Center only performs breathing relaxation techniques to reduce pain during labor. One of the non-pharmacological methods that are very effective in dealing with pain is kneading massage, counterpressure and kneading and counterpressure. The purpose of this study was to analyze the effectiveness of kneading massage, counterpressure and kneading and counterpressure to reduce pain intensity in the first stage of active labor. This research method uses a quasi-experimental method with a three-group pretest-posttest design with a sample of 30 respondents using purposive sampling technique. Data collection using NRS questionnaire, SOP massage kneading, counterpressure and kneading and counterpressure. Data analysis used univariate and bivariate. The results of statistical tests, it can be concluded that massage kneading (p = 0.004), counterpressure (p = 0.004), and the combination of kneading and counterpressure (p = 0.002) are effective in reducing pain intensity in the first stage of labor in the active phase. There was no difference in effectiveness between the three massages in reducing the intensity of labor pain in the first active phase (p = 0.485).